2022
DOI: 10.1177/26350106221100779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Digitally Enhanced Diabetes Self-Management Program on Glycemia and Medical Costs

Abstract: Objective: To analyze economic savings and health impacts associated with a virtual digitally enhanced diabetes self-management education and support (DSMES) program. Research design and methods: Participants (n = 1,494) were nonpregnant adults with diagnosed type 2 diabetes and baseline body mass index (BMI) of 25 kg/m2 (23 kg/m2 if of Asian descent) or higher who enrolled in virtual DSMES between February 2019 and April 2020 for at least 4 months. Participants’ changes in glycated hemoglobin (A1C) and body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…28 A recent analysis also revealed that participation in this program significantly improves A1C and body weight within 6 months, with the potential to slow onset of diabetes sequelae and reduce medical expenditures. 29 Although it is evident that participation in Omada for Diabetes has clinical and cost-saving benefits, research assessing real-world evidence outcomes over a longer period of time is warranted. Therefore, the primary objective of this study is to evaluate the impact of Omada for Diabetes on A1C across 12 months, overall and stratified by A1C at baseline (≥8% vs <8%).…”
mentioning
confidence: 99%
“…28 A recent analysis also revealed that participation in this program significantly improves A1C and body weight within 6 months, with the potential to slow onset of diabetes sequelae and reduce medical expenditures. 29 Although it is evident that participation in Omada for Diabetes has clinical and cost-saving benefits, research assessing real-world evidence outcomes over a longer period of time is warranted. Therefore, the primary objective of this study is to evaluate the impact of Omada for Diabetes on A1C across 12 months, overall and stratified by A1C at baseline (≥8% vs <8%).…”
mentioning
confidence: 99%
“…Primary outcomes of DSMES include (i) improved T2DM self-efficacy, (ii) increased diabetes knowledge, (iii) glycemic control of hemoglobin A1c (HbA1c), (iv) reduced symptoms of anxiety and depression, and (v) enhanced quality of life (Kavookjian et al, 2022;Tanaka et al, 2020). Benefits of DMSES include improved health behaviors and health outcomes such as prevention and delay of complications and improved hemoglobin A1C levels (Chen et al, 2022;Okeyo et al, 2023). Although clinical benefits of DMSES have been demonstrated, DSMES services remain widely underused (James, 2021).…”
mentioning
confidence: 99%